2007
DOI: 10.1111/j.1528-1167.2006.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Anterior Nucleus of the Thalamus for Intractable Epilepsy: A Long‐term Follow‐up Study

Abstract: Summary:Purpose: The anterior nucleus of the thalamus (ANT) modulates temporal lobe and hypothalamic activities, and relays information to the cingulate gyrus and entorhinal cortex. Deep brain stimulation (DBS) of the ANT has been reported to decrease seizure activity in a limited number of human subjects. However, long-term effect of chronic ANT stimulation on such patients remains unknown. We report long-term follow-up results in four patients receiving ANT stimulation for intractable epilepsy.Methods: Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
164
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(183 citation statements)
references
References 28 publications
7
164
0
3
Order By: Relevance
“…The treatment group of the 110 patients in the SANTE trial showed a median seizure frequency reduction of 29% at 3 months, 41% at 1 year, 56% at 2 years, and 68% by the end of 3 years as compared with baseline. Other, smaller, nonrandomized trials of ANT stimulation also have been performed with 4–6 patients per trial, with seizure frequency reduction of 14–75% 9, 11, 16, 17, 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…The treatment group of the 110 patients in the SANTE trial showed a median seizure frequency reduction of 29% at 3 months, 41% at 1 year, 56% at 2 years, and 68% by the end of 3 years as compared with baseline. Other, smaller, nonrandomized trials of ANT stimulation also have been performed with 4–6 patients per trial, with seizure frequency reduction of 14–75% 9, 11, 16, 17, 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…Finally, considering our experiences in this open-pilot DBS study in patients with PME, we strongly recommended further investigation of this therapeutic approach by means of a multicenter study considering off-phases and assessing the effect of the surgical procedure itself by initiating DBS sometime after surgery as it was elegantly performed by others applying DBS in epilepsy (Lim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the anterior nucleus of the thalamus has so far been tested in about 31 patients worldwide with multifocal epilepsy and symptomatic generalised seizures or partial complex [18][19][20][21][22][23]. These studies report that stimulation at a frequency between 90 and 200 Hz, produces a significant reduction of theseizure frequency (≥60%) in 16/31 of the patients.…”
Section: Deep Brain Stimulationmentioning
confidence: 98%